Competitiveness Sensitivity of Oil Palm Farming on Suboptimal Land at Musi Rawas Residence - Verry Yarda Ningsih; Nenny Wahyuni; Nila Suryati; Noviyanto Noviyanto; Heriyanto Heriyanto (Jurnal Ilmu dan Teknologi Terapan Pertanian, 2020)
Palm oil is an edible vegetable oil derived from the mesocarp (reddish pulp) of the fruit of the oil palm, primarily the African oil palm Elaeis guineensis. Oil palm is one of agriculture comodity that can increase farmers income, provide raw material on manufacture industry which can create added value. The expansion of oil palm farming in Indonesia has shifted the use of mineral land to suboptimal land which is currently available in many place in Indonesia. Generally the aim of this research is to anylize the competitiveness sensitivity of oil palm farming. Specifically this research wants to anylize the sensitivity on input-output changing, and to anylize the impact of government policy on input-output when facing fluctuation price. In order to reach the goal of this research we used Policy Anlayisis Matrix (PAM). The result of this research shows that partially the declining of price, declining of output volume and increasing input price PCR value and DRCR < 1, which means that the oil palm farming on suboptimal land has competitivenes, and the absence of government policy on determaining input price nor output price on oil palm farming in at suboptimal land. While simultanously shows that the fluctuation of input and output price causes value of PCR dan DRCR > 1 with PCR value 1,12 and DRCR value 1,04, means that oil palm farming on suboptimal land at Musi Rawas Regency not feasible and has no competitiveness. It means that government policy needed to protect input price in oil palm farming on suboptimal land. Therefore government support and guidence in oil palm farming technology on suboptimal land also needed to increase the production of oil palm farming on suboptimal land.